Population Parameters as Key Factors for Site-Specific Distribution of Invasive Weed Rhynchosia senna in Semiarid Temperate Agroecosystems - Quintana, Matias; Chantre Balacca, Guillermo Ruben; Reinoso, Omar Juan; Renzi Pugni, Juan Pablo (MDPI, 2025)
The genus Rhynchosia includes more than 550 species, some exhibiting invasive behavior. Rynchosia senna var. senna (RS) is a challenging weed to control in its native range; however, its invasive potential remains unknown. The aim of this study was to evaluate RS demographic parameters to determine its invasive potential, including (i) plant fecundity during the first year of young adult and in adult plants, (ii) seed dispersal, (iii) pre- and post-dispersal predation, (iv) soil seedbank persistence, and (v) field emergence patterns. RS fecundity declined in autumn and mainly in early established cohorts. Fecundity was influenced by pre-dispersal predation (Bruchus spp. 12 ± 2%), and post-dispersal removal by birds (66 ± 4%) and arthropods (37 ± 5%). Seed dispersal decreased with distance. Seedling emergence occurred mainly during early summer (75%), and to a lesser extent during late summer (20%) and autumn (5%). Seed physical dormancy loss (~80% in the first year) defines a short persistent seedbank. Under the evaluated conditions (native environment), RS shows a limited invasive potential. However, in non-native environments, in the absence of natural predators, its prolific fecundity and the occurrence of staggered emergence patterns could easily enhance invasiveness, enabling rapid colonization, as observed in Medicago polymorpha L.